Prospects of Kiulu 4M Challenge (K4MC) in promoting Sabah as a toursm destination / Jarahim Jahim - Jahim, Jarahim (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2000)
This Project paper is about the marketing research on how Sabah is being promoted through the K4MC sport event. The K4MC highlights on the usage of the river and the bamboos as its main field of competition. The importance of the river and the bamboos in the traditional livelihood of the natives, particularly the Kadazan Dusuns, possess rich socio-cultural-economic touristic values. This research is needed because we want to know whether the K4MC could pose as raw challenge to visitors who may want to sample the traditional sports and pastimes of the Sabah natives on land and water. The researcher also wanted to know whether the event could be promoted as an environmental conservation of natural surroundings, as well as making Kiulu a popular tourist destination. This research is conventional research using hypothesis testing where questionnaire is used to investigate through the cross tabulation of the prospects of the K4MC in promoting Sabah as a tourism destination.